The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1371/journal.pone.0150099
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Changes during Overwintering at the German Antarctic Stations Neumayer II and III: The Gender Factor

Abstract: PurposeAntarctic residence holds many challenges to human physiology, like increased psycho-social tension and altered circadian rhythm, known to influence sleep. We assessed changes in sleep patterns during 13 months of overwintering at the German Stations Neumayer II and III from 2008 to 2014, with focus on gender, as many previous investigations were inconclusive regarding gender-based differences or had only included men.Materials & MethodsTime in bed, sleep time, sleep efficiency, number of arousals, slee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 89 publications
(122 reference statements)
5
29
0
1
Order By: Relevance
“…Moreover, concordant to Steinach et al [43], physical activity in females stayed balanced during the study period as displayed on the hormonal level by continuously low excreted masses of norepinephrine and epinephrine and therefore has to be excluded as potential explanation for the high cortisol concentrations. The nearly constantly higher masses of both catecholamines in males compared to females, particularly in the daytime urine collection, may be explained by the fact that the physically most strenuous work on-site Antarctic research stations is predominantly done by men (e.g., technicians).…”
Section: Differential Neurohumoral Response Pattern and Psychologicalsupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, concordant to Steinach et al [43], physical activity in females stayed balanced during the study period as displayed on the hormonal level by continuously low excreted masses of norepinephrine and epinephrine and therefore has to be excluded as potential explanation for the high cortisol concentrations. The nearly constantly higher masses of both catecholamines in males compared to females, particularly in the daytime urine collection, may be explained by the fact that the physically most strenuous work on-site Antarctic research stations is predominantly done by men (e.g., technicians).…”
Section: Differential Neurohumoral Response Pattern and Psychologicalsupporting
confidence: 72%
“…Recently, Steinach et al [43] notably observed a declined sleep quality (increase of time in bed, decline in sleep efficiency, increase in number of arousals) in females during a total of seven overwintering campaigns at the German Antarctic Station Neumayer II/III from 2008 to 2014. Against the background of the demonstrated interaction of sleep and HPA activity, these findings support our results of higher cortisol concentrations in females during three overwintering campaigns at Neumayer III.…”
Section: Differential Neurohumoral Response Pattern and Psychologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender aspects in sleep quality have been studied in the Neumayer Antarctic stations [ 43 ]. Thus, overwinterings at the stations Neumayer II and III are associated with significant changes in sleep patterns, with dependences from overwintering time and local sunshine radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, overwinterings at the stations Neumayer II and III are associated with significant changes in sleep patterns, with dependences from overwintering time and local sunshine radiation. Gender appears to be an influence, as women showed a declining sleep quality, despite that their physical activity remained unchanged, suggesting other causes such as a higher susceptibility to psycho-social stress and changes in environmental circadian rhythm during long-term isolation in Antarctica [ 43 ].…”
Section: Resultsmentioning
confidence: 99%